Transcranial Doppler to detect right‐to‐left shunt in cryptogenic acute ischemic stroke. Issue 1 (1st December 2018) - Palazzo, Paola; Ingrand, Pierre; Agius, Pierre; Belhadj Chaidi, Rafik; Neau, Jean‐Philippe
Abstract: Objectives: We aimed to confirm the sensitivity and specificity of contrast transcranial Doppler (cTCD) in the detection of right‐to‐left shunt (RLS) compared to the current reference standard (i.e., transesophageal echocardiography—TEE) in patients aged <55 years with a cryptogenic acute ischemic stroke (AIS) or high‐risk (ABCD 2 score ≥4) transient ischemic attack (TIA), and to calculate the real life delay in detecting RLS by cTCD versus TEE in a tertiary care academic stroke center. Methods: Consecutive 16‐ to 54‐year‐old patients with AIS or high‐risk TIA underwent complete diagnostic workup which included, in case of undetermined etiology, cTCD and TEE. Sensitivity and specificity of cTCD, RLS characteristics, and median delay between the two tests were calculated. Results: Of the 98 included patients, 52 (53%) had a cryptogenic cerebrovascular ischemic event, which displayed a 56% prevalence of RLS related to a patent foramen ovale (PFO) mainly with a high‐grade shunt. When comparing TCD with "bubble test" to TEE, sensitivity and specificity were both 100%. Median delays from symptom onset to examination were 2 (min–max 1–10) and 21 (min–max 1–60) days, respectively, for cTCD and TEE. No adverse event occurred during or after cTDC examination. Conclusions: Transcranial Doppler with "bubble test" appears as the best screening test for the detection of RLS in young and middle‐aged adults with cryptogenic acute cerebral ischemic events to select patients potentially suitable for closure procedure after TEE confirmation. Abstract : Contrast transcranial Doppler (cTCD) showed 100% sensitivity and specificity in the detection of right‐to‐left shunt (RLS) compared to the current reference standard (i.e., transesophageal echocardiography—TEE) in consecutive patients aged <55 years with a cryptogenic acute ischemic stroke or high‐risk transient ischemic attack. Median delays from symptom onset to examination were 2 (min–max 1–10) and 21 (min–max 1–60) days, respectively, for cTCD and TEE. Transcranial Doppler with "bubble test" appears as the best screening test for the detection of RLS in young and middle‐aged adults with cryptogenic acute cerebral ischemic events to select patients potentially suitable for closure procedure after TEE confirmation.